Prevalence and Determinants of Postpartum Depression in Sukoharjo District, Central Java - Putriarsih, Ryanawati; Budihastuti, Uki Retno; Murti, Bhisma (Journal of Maternal and Child Health, 2018)
Background: After delivery of psychological disorder otherwise appropriately and immediately handled may lead to postpartum depression (PPD). PPD has a serious impact on mothers that manifests as lower quality of life and inability to care of themselves, their partner, and infants. There is a lack of studies on PPD in Indonesia. Its prevalence and determinants are not well-understood. This study sought to estimate the prevalence and the determinants of PPD in Sukoharjo, Central Java. Subjects and Method: This was an analytic observational study with a cross-sectional design. The study was conducted at community health centers in Sukoharjo District, Central Java, from November to December 2017. A total sample of 200 postpartum mothers was selected for this study using cluster random sampling, with a community health center as the cluster. The dependent variable was PPD. The independent variables were maternal age, parity, labor complication, maternal education, self-efficacy, family income, coping strategy, unwanted pregnancy, and family support. The data were collected by questionnaire and analyzed by path analysis. Results: PPD prevalence in Sukoharjo, Central Java, was 18.5%. The risk of PPD increased with labor complication (b= 3.14, SE= 0.45, p<0.001), unwanted pregnancy (b= 1.54, SE= 0.45, p<0.001), and low family income (b= -0.05, SE= 0.01, p<0.001). The risk of PPD decreased with age (b= -0.07, SE= 0.03, p= 0.028), stronger self-efficacy (b= -0.55, SE= 0.09, p<0.001), and improved coping strategy (b= -0.56, SE= 0.03, p= 0.064). PPD was indirectly affected by younger age, parity, weaker family support, lower family income, coping strategy, and maternal education. Conclusion: PPD prevalence is 18.5% in Sukoharjo, Central Java. The risk of PPD increases with labor complication, unwanted pregnancy, and low family income, but decreases with age, stronger self-efficacy, and improved coping strategy. Keyword: prevalence, postpartum depression, determinant, path analysis Correspondence: